1984
DOI: 10.1016/0035-9203(84)90172-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of single-dose oral treatment in schistosomiasis haematobium

Abstract: A two-year follow-up was conducted in children who had been the subjects of a six-month double-blind trial in the single-dose treatment of Schistosoma haematobium infection. The trial had assessed therapeutic efficacy of three oral preparations-praziquantel 40 mg/kg, metrifonate 10 mg/kg, and the 'combination' (concurrent niridazole 25 mg/kg and metrifonate 10 mg/kg administration). Reduction in urinary egg excretion remained high up to follow-up at two years, based on a comparison of pre- and post-treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Stephenson 1989 KEN reported treatment failure at eight months, its only time point. A single dose of praziquantel reduced treatment failure by 86% compared to placebo (RR 0.14, 95% CI 0.08 to 0.22; 209 participants, one trial, Analysis 1.1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stephenson 1989 KEN reported treatment failure at eight months, its only time point. A single dose of praziquantel reduced treatment failure by 86% compared to placebo (RR 0.14, 95% CI 0.08 to 0.22; 209 participants, one trial, Analysis 1.1).…”
Section: Resultsmentioning
confidence: 99%
“…Percent egg reduction was variable in the placebo group, ranging from 26% increase to 54% reduction at three months and from 5% to 64% reduction at six months (see Table 4). One additional trial, Stephenson 1989 KEN, reported percent egg reduction at eight months as its only time point (209 participants, see Table 4). Percent egg reduction after praziquantel was 99% compared to 5% with placebo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although praziquantel is the drug of choice for the treatment of S. haematobium infections (Gentilini et al 1982, McMahon 1983, Pugh & Teesdale 1984, Stephenson et al 1989, McNeeley et al 1990, King et al 1992, King & Mahmoud 1999, King et al 2002, cases of treatment failure have been frequently reported, probably due to a progressive increase in the resistance of the parasite to the drug, as observed by some authors (Groning et al 1985, Herwaldt et al 1995, Hatz et al 1998, Ernould et al 1999, Liang et al 2000. Despite the controversies regarding the rapid emergence of praziquantel resistance, constant surveillance of this progression is important.…”
Section: Discussionmentioning
confidence: 99%
“…10 We observed a 90% cure rate in patients with S. haematobium infection who were treated with metrifonate, and this is comparable to the rates reported in other studies. [12][13] Oxamniquine in different dosages has been used in different parts of the world to treat schistosomiasis. 14,15 The cure rate in our study was 91%.…”
Section: Discussionmentioning
confidence: 99%